ANALISIS YURIDIS PENERAPAN HUKUM TERHADAP TINDAK PIDANA PERDAGANGAN ORANG - Fitriana Halawa (LPPM Universitas Nias Raya, 2026)
Trade in people is all forms of buying and selling transactions against humans. The criminal act of trafficking in people is generally in the form of violations of dignity, dignity and human rights in the form of cruel treatment and damaging the morals of victims. This treatment is accepted as the helplessness of victims trapped in network entanglement that is very difficult to identify so that it will be difficult to find a solution. One of the criminal acts of trafficking in persons who have been tried and in tried and examined by the Tanjung Selor District Court, namely Decision Number 87/Pid.Sus/2023/PN. Tjs, where in the decision the judge sentenced him to imprisonment for 8 (eight) months for violating Article 506 of the Criminal Code concerning pimping (sounteneur) based on the fourth alternative charge. The research used is normative research with data collection techniques using primary data, secondary data, and tertiary data. Secondary data obtained in this study, Obtained in this study, the author analyzed using qualitative analysis methods which were then compiled descriptively and drew conclusions using deductive methods. Based on research findings and discussion of the application of the law to the criminal act of trafficking in people who use and facilitate the occurrence of sexual intercourse so that they can benefit from the results of these acts, which according to the author imposes criminal sanctions That's not right. So according to the author that in Decision Number 87/Pid.Sus/2023/PN. Tjs, the panel of judges should apply the law in accordance with the first alternative charge, namely Article 2 paragraph (1) of Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons. Based on the principle of lex spcesialis derogat lex generalis where general rules are overridden by specific regulations.